Cyclin A2 localises in the cytoplasm at the S/G2 transition to activate PLK1 - Silva Cascales, Helena; Burdova, Kamila; Middleton, Anna; Kuzin, Vladislav; Müllers, Erik; Stoy, Henriette; Baranello, Laura; Macurek, Libor; Lindqvist, Arne (Life science alliance, 2021)
Cyclin A2 is a key regulator of the cell cycle, implicated both in DNA replication and mitotic entry. Cyclin A2 participates in feedback loops that activate mitotic kinases in G2 phase, but why active Cyclin A2-CDK2 during the S phase does not trigger mitotic kinase activation remains unclear. Here, we describe a change in localisation of Cyclin A2 from being only nuclear to both nuclear and cytoplasmic at the S/G2 border. We find that Cyclin A2-CDK2 can activate the mitotic kinase PLK1 through phosphorylation of Bora, and that only cytoplasmic Cyclin A2 interacts with Bora and PLK1. Expression of predominately cytoplasmic Cyclin A2 or phospho-mimicking PLK1 T210D can partially rescue a G2 arrest caused by Cyclin A2 depletion. Cytoplasmic presence of Cyclin A2 is restricted by p21, in particular after DNA damage. Cyclin A2 chromatin association during DNA replication and additional mechanisms contribute to Cyclin A2 localisation change in the G2 phase. We find no evidence that such mechanisms involve G2 feedback loops and suggest that cytoplasmic appearance of Cyclin A2 at the S/G2 transition functions as a trigger for mitotic kinase activation.
Keywords: proteiny buněčného cyklu; chromatin; mitóza; fosforylace; Mitosis; S Phase; cyklin-dependentní kinasa 2; HeLa buňky; Phosphorylation; poškození DNA; Chromatin; cytoplazma; aktivace enzymů; Enzyme Activation; vazba proteinů; HeLa Cells; protein-serin-threoninkinasy; Humans; DNA Damage; Cytoplasm; polo-like kinasa 1; G2 Phase; buněčné jádro; Cell Nucleus; Cyclin A2; Cell Cycle Proteins; proteinkinasa CDC2; S fáze; CDC2 Protein Kinase; Polo-Like Kinase 1; cyklin A2; Protein Serine-Threonine Kinases; Cyclin-Dependent Kinase 2; G2 fáze; transfekce; lidé; Signal Transduction; protoonkogenní proteiny; Proto-Oncogene Proteins; Protein Binding; Transfection; signální transdukce